Anesthetic Management of a Patient With Jarcho-Levin Syndrome - Gamze Küçükosman; Bengü Gülhan Aydın; Aslı Yalçın; Hilal Peri Ayoğlu (Haseki Tıp Bülteni)
Jarcho-Levin syndrome (JLS) is a rare disease involving costovertebral anomalies and is accompanied by hydrocephalus, neural tube defect, and cardiac, renal and gastrointestinal problems. Due to respiratory system pathologies, there is a high mortality rate at young ages. Due to its rarity and little information in the literature related to anesthetic practice for this syndrome, we present our anesthetic experience of inguinal hernia surgery in a patient with JLS.